The appearance of the emerging corona virus in contemporary Iraqi painting / selected models - Assistant Professor Dr. Hazem Aboudi Al-Saidi (Periodica Journal, 2022)
The research studies the manifestations of the Corona virus in contemporary Iraqi painting. The nature of the concept of the manifestations resulted from the outbreak of Covid 19 and dealt with it in Iraqi painting by contemporary artists in three sections. The first is the definition of Corona virus, the second is Corona virus in Iraqi painting and the third is selected models, the research contained planned and colored illustrations. In watercolor and oil, analyzing the artworks published on the pages of artists and the Iraqi, international and Arab press, the research aims to identify the manifestations of the virus in Iraqi painting, where the research community is determined by an elected group of artists within the Artists Syndicate and the Iraqi Plastic Society of Karbala branch. It included (8) artists and the research sample consisted of (8) selected by experts specialized in art education and plastic arts, and the researcher reached the following results: 1. Artists have a delicate sense and a high level of intelligence to deal with the shape of the virus. 2. There is a positive relationship between the virus and the artist in light of the transformations of formal appearance. 3. The depiction of the virus prevailed in the media and methodically.
Keywords: Iraqi painting